2018
DOI: 10.3389/fphar.2018.00705
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypic and Genotypic Association of Catechol-O-Methyltransferase rs4680 and rs4818 Polymorphisms and Treatment Resistance in Schizophrenia

Abstract: Treatment-resistant schizophrenia (TRS) continues to be a challenge. It was related to different factors, including alterations in the activity of brain dopaminergic system, which could be influenced by the dopamine-degrading enzyme, catechol-O-methyltransferase (COMT). Variants of the COMT gene have been extensively studied as risk factors for schizophrenia; however, their association with TRS has been poorly investigated. The aim of the present study was to determine the haplotypic and genotypic association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 116 publications
(176 reference statements)
4
17
1
2
Order By: Relevance
“…In our previous study on the treatment resistant schizophrenia 7 , the G alleles of the COMT rs4680 and rs4818, as well as the high activity COMT G-G/G-G haplotype, had lower risk to become treatment resistant only in female but not in male patients with schizophrenia. In contrast to these data 7 , in the present study the genotype distribution for the COMT rs4680 and rs4818 did not differ according to gender. However, when male and female subjects were evaluated separately, no significant association was detected between the COMT rs4680 and rs4818 genotypes and haplotypes and treatment response to olanzapine, risperidone, clozapine or other antipsychotics (Supplementary Tables S1-S12).…”
Section: C-a Haplotype Carriers C-a Carriers Non-carriers C-a Carriercontrasting
confidence: 99%
See 3 more Smart Citations
“…In our previous study on the treatment resistant schizophrenia 7 , the G alleles of the COMT rs4680 and rs4818, as well as the high activity COMT G-G/G-G haplotype, had lower risk to become treatment resistant only in female but not in male patients with schizophrenia. In contrast to these data 7 , in the present study the genotype distribution for the COMT rs4680 and rs4818 did not differ according to gender. However, when male and female subjects were evaluated separately, no significant association was detected between the COMT rs4680 and rs4818 genotypes and haplotypes and treatment response to olanzapine, risperidone, clozapine or other antipsychotics (Supplementary Tables S1-S12).…”
Section: C-a Haplotype Carriers C-a Carriers Non-carriers C-a Carriercontrasting
confidence: 99%
“…The differences between these studies are in the design, since present study was longitudinal while our previous study was cross-sectional, and, unlike the current investigation, previous study did not exclude patients who received ECT, as well as different antipsychotic combinations 7 . Large heterogeneity across studies, adherence to treatment, population stratification 6 , as well as influence of other functional variants in the COMT gene 7,31,32 , interactions with other gene polymorphisms, such as DRD4 (120-bp duplication) 33 , might explain some of the inconsistent findings. In addition, recent studies 34,35 discussed the disadvantages of the candidate gene association studies compared to genome-wide association studies (GWAS), pointing to the problems of high false discovery rate, low replication rates and insufficient knowledge to correctly identify possible candidate genes.…”
Section: C-a Haplotype Carriers C-a Carriers Non-carriers C-a Carriermentioning
confidence: 88%
See 2 more Smart Citations
“…57 A study of two single-nucleotide polymorphisms (SNPs) in the dopamine-degrading enzyme catechol-O-methyltransferase (COMT) demonstrated that a higher-activity haplotype was protective against TRS in women but not men. 58 Genetic polymorphisms in DRD2 may also affect a patient's risk of developing DSP TRS or the likelihood that a patient will respond to non-clozapine antipsychotic medications. 36,59 However, another study showed no association between TRS and SNPs in DRD1, DRD2, DRD3, or COMT.…”
Section: Genetic Variants That May Contribute To Schizophrenia or Trsmentioning
confidence: 99%